Use of refurbished shipping containers for the construction of housing buildings: details for the structural project - Bernardo, Luís F. A.; Oliveira, Luiz A. P.; Nepomuceno, Miguel C. S.; Andrade, Jorge M. A. (Journal of Civil Engineering and Management, 2013)
Construction using refurbished shipping containers is a recent building system, with already many successful examples around the world. This system presents a huge potential in the field of sustainable construction provided by the recycling of used containers. This paper aims to contribute to a better knowledge of this construction system in what concerns to the structural project. The general constitution of two maritime shipping containers is presented as well as some aspects of their structural behavior. For this purpose, numerical analyses were performed using a finite elements analysis program. Normative aspects for the structural project are also presented. This paper also presents the analysis of a case study with the use of refurbished shipping containers to build a single-family house. The evaluation of the strength of the refurbished shipping containers to building actions is carried out. It is shown that such evaluation is not easy because some mechanical parameters of noncommercial steel section of the elements that compose the shipping containers are unknown. Nevertheless, this study shows the feasibility of this building system.